Youth Underemployment in Sulawesi - Ahmad Ayis; Lilik Sugiharti (Gorontalo Development Review, 2021)
Underemployment provides a picture of the imperfection of the labor market which causes the capacity of the workforce to be unable to be optimally utilized. Many studies state that young workers are very vulnerable to being underemployed. Youth is the driving force of a country's economic development, so the labor problems inherent in youth must be resolved properly. This study aims to analyze the factors affecting underemployment among young people in Sulawesi Island. The data used in this research is SAKERNAS August 2019 data. The method of analysis used is multinomial logistic regression analysis, where the independent variables of this study are variables related to the individual and occupational characteristics of the young population. This research shows that there are differences in the factors that affect underemployment of young men and women, especially in education and business. The weakness of this research is the unavailability of micro data that can describe labor market conditions.